Graphene Oxide Based P-N Junctions. (2019) - Ranjan, Pranay; Kumar, Atul; Balakrishnan, Jayakumar; Thakur, Ajay D.
Abstract: We demonstrate the use of graphene oxide (GO) in making p-n junctions. Two variants of p-n junctions made using GO are reported. In one of the variant, we deposit a layer of GO on aluminium zinc oxide (AZO) and study the junction properties using current-voltage (I-V) characteristics. In the other variant, we reduce the GO deposited on a glass substrate to obtain reduced graphene oxide (rGO) and make a GO-rGO bilayer p-n junction. The photovoltaic response of this GO-rGO bilayer is reported. These two approaches provide an inexpensive route to make p-n junctions for realizing GO based electronic devices.